(3ESGAI GSJYeGd GdSdWI GdEOGQjI (B/s - (3QjGV, CMeO QRb,s 1979- ((3GdEScfOQjI (B[(3eUQ(B] :s (3ecJHI GdhaGA GdbGfhfjI,s, 2010)
(3hjJVef GdcJGH GNJUGU GdbVGA GdEOGQj HOYGhi ESGAI GSJYeGd GdSdWI, hCMbjI GdeJVQQ ef GdbQGQGJ GdeThHI HESGAI GSJYeGd GdSdWI aj GdJYhjV Yfg efGWg JhGaQ CQcGf GdeSFhdjI, hfWGb CYeGd GdHQdeGf GdEOGQjI ef QbGHI GdbVGA Ydi ESGAI GSJYeGd GdSdWI, hYjH ESGAI GSJYeGd GdSdWI YjH bUOj jTJQW ajg GdJYeO, hGdbQGQ GdeYjH HESGAI GSJYeGd GdSdWI jZGjQ GdbQGQ GdPj jYJQjg NWC eGOj, EPG TGH ESGAI GSJYeGd GdSdWI CMO GdbQGQjf dG jYfj Cf jHWd cdGgeG eJi cGfG eNJdajf ZjQ efOeLjf(B.s
(3HHdjhLQGajI (B: (3UaMI (B343-351.s
Keywords: (3GdELQGAGJ GdEOGQjIs -- (3bhGfjf hJTQjYGJs -- (3eUQs; (3GdSdWI GdEOGQjIs -- (3bhGfjf hJTQjYGJs -- (3eUQs; (3GdbGfhf GdEOGQjs -- (3eUQs